To complete the square, remember the formula for a square binomial:
![(x+a)^2=x^2+2ax+a^2](https://img.qammunity.org/2023/formulas/mathematics/high-school/eea9ekuwxh56h7u1b1fy8euvjkof1ed9ma.png)
The coefficient of the linear term is 2a. In this case:
![x^2-x=4](https://img.qammunity.org/2023/formulas/mathematics/college/82n5v9kjqul6yd1xe1qu1aquftwu4pt1d1.png)
We can see that the coefficient of the linear term on the left member of the equation is -1. Then:
![\begin{gathered} 2a=-1 \\ \Rightarrow a=-(1)/(2) \\ \Rightarrow a^2=(1)/(4) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/8v32xza7xiuudu0tiphg8aoetfg8hyvufr.png)
Add and substract 1/4 to the left member of the equation:
![x^2-x+(1)/(4)-(1)/(4)=4](https://img.qammunity.org/2023/formulas/mathematics/college/ur04mdl2ru8gplypp8osqzk223e6sjkkip.png)
Since the first three terms of the left member correspond to a perfect square trinomial, then we can rewrite it as a square binomial:
![\begin{gathered} x^2-x+(1)/(4)=(x-(1)/(2))^2 \\ \Rightarrow(x-(1)/(2))^2-(1)/(4)=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/n59xmkyd4qoqlypm7as0xhjvxydgp0ebl8.png)
Add 1/4 to both sides of the equation:
![\begin{gathered} \Rightarrow(x-(1)/(2))^2=4+(1)/(4) \\ \Rightarrow(x-(1)/(2))^2=(17)/(4) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/g84i65kyazgsjx2oprud0r8089i2s3wjbe.png)
Take the square root to both sides of the equation:
![\begin{gathered} \Rightarrow\sqrt[]{(x-(1)/(2))^2}=\sqrt[]{(17)/(4)} \\ \Rightarrow x-(1)/(2)=\pm\frac{\sqrt[]{17}}{2} \\ \Rightarrow x=\pm\frac{\sqrt[]{17}}{2}+(1)/(2) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/a3m9z12f0rce6v9sfzyhda3u0a2iu7nhl5.png)
Therefore, the answer is:
![x=\pm\frac{\sqrt[]{17}}{2}+(1)/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/5jm5mggl7fmntkwaxccs4mwmic373bk02c.png)